Functionalized MoS2 Nanosheet‐Based Field‐Effect Biosensor for Label‐Free Sensitive Detection of Cancer Marker Proteins in Solution. Issue 6 (29th January 2014) - Wang, Lu; Wang, Ye; Wong, Jen It; Palacios, Tomás; Kong, Jing; Yang, Hui Ying
<x xml:space="preserve">Abstract</x> Label‐free MoS2 nanosheet‐based field‐effect biosensor detects cancer marker protein Prostate Specific Antigen in real time with high sensitivity and selectivity, exhibiting great potential in point‐of‐care diagnostics application. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>